Corporate Learning Preparing the Implementation of Corporate Strategy - Agus Hekso Pramudijono (Universitas Negeri Malang, 2015)
Abstract: At present there are needs to transform how organizations develops their human resources, to be more technological savy, efficient and implement alternative approach such as e-learning. Cor-porate e-learning provides the option for organizations to holds training anywhere, anytime and for anyone. By maximizing these facilities, organizations should be able to distribute training and critical information to multiple locations easily and conveniently. Thus, ensuring access of human capital development from work or even from home. This paper discusses the Electronic Learning Circles in FETA Learning Network in the light of corporate learning theory. According to the paper, the benefits of e-Learning are as follows ; 1) the substantial saving of resources from the elimination of travel ex-penses; 2) just-in-time access to timely information; 3) the creation of higher retention of content through personalized learning for the employees; 4) corporate e-Learning improve collaboration and interaction between students and lecturers; 5) online training is less intimidating than instructor-led courses. Key Words: corporate learning strategy, e-learning, cost efficient training, human capital development Abstrak: Sekarang ini kebutuhan suatu organisasi dalam transformasi pengembangkan sumber da-ya manusia, untuk lebih melek teknologi, efisien, adalah dengan alternatif  penerapan menggunakan pendekatan seperti e-learning. Corporate e-learning memberikan pilihan bagi organisasi untuk melaku-kan pelatihan di mana saja, kapan saja dan untuk siapa saja. Dengan memaksimalkan fasilitas ini, or-ganisasi mampu mendistribusikan pelatihan dan informasi penting untuk beberapa lokasi dengan mudah dan nyaman. Sebuah organisasi dapat memastikan akses dalam pengembangan sumber daya manusia dari tempat kerja atau bahkan dari rumah. Tulisan ini membahas Siklus Pembelajaran Elektronik pada Jaringan Belajar di Badan Pendidikan dan Pelatihan Keuangan tentang corporate learning theory. Hasil menunjukkan bahwa manfaat dari e-learning adalah sebagai berikut. 1) Penghematan besar sumber daya dari penghapusan biaya perjalanan. 2) Just-in-time akses ke informasi yang tepat waktu. 3) Tempat penyimpanan konten yang lebih besar untuk pembelajaran pribadi bagi karyawan. 4) Corporate e-learning meningkatkan kolaborasi dan interaksi antara mahasiswa dan dosen. 5) Pe-latihan online kurang mengintimidasi daripada program yang dipimpin oleh instruktur. Kata kunci: strategi pembelajaran perusahaan, e-learning, biaya pelatihan yang efisien, pengembang-an sumber daya manusia